2022
DOI: 10.1021/acs.joc.1c02783
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(II)/Lewis Acid-Catalyzed Olefination of Arylacetamides with Dioxygen

Abstract: The present work introduces Pd(II)/LA-catalyzed (LA: Lewis acid) olefination of arylacetamides with dioxygen as the oxidant source. This protocol tolerates with different functional groups on the substrates, and the catalytic efficiency is highly Lewis acidity-dependent on added LA, that is, a stronger LA provided a better promotional effect. The 1 H NMR studies of the semireaction between the arylacetamide and the Pd(II)/Sc(III) catalyst in HOAc-d 4 disclosed the formation of a palladacycle intermediate, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…However, by treating 1a with 1 equiv of Pd­(OAc) 2 /Sc­(OTf) 3 , its 1 H NMR signals changed completely, giving three sets of aromatic protons that belong to three compounds 2 , 3 , and 4 (Figure c). As shown, compound 2 was assigned to an aromatic η 2 -complex of Pd­(II)/Sc­(III) in which the Pd­(II)/Sc­(III) core was a diacetate-bridged heterometallic unit as well as that in previous studies. ,, The presence of the Pd­(II)/Sc­(III) core in 2 , 3 , and 4 was also indicated by 19 F NMR studies that showed their identical 19 F chemical shifts to that of Pd­(OAc) 2 /Sc­(OTf) 3 in MeCN, thus indicating that they had the identically chemical environment (see Figure S60 in the Supporting Information for details). The Pd­(II)/Sc­(III) core was linked to 1a through its directing N -carbonyl group with unsymmetrical η 2 -coordination at the aromatic C 1  C N bond, which caused the chemical shift of H1 significantly upshifting from 7.26 to 7.03 ppm due to the shielding effect of Pd­(II), while H2 and H3 slightly downshifted from 6.99 and 6.84 ppm to 7.08 and 6.89 ppm, respectively, due to the corresponding deshielding effect.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…However, by treating 1a with 1 equiv of Pd­(OAc) 2 /Sc­(OTf) 3 , its 1 H NMR signals changed completely, giving three sets of aromatic protons that belong to three compounds 2 , 3 , and 4 (Figure c). As shown, compound 2 was assigned to an aromatic η 2 -complex of Pd­(II)/Sc­(III) in which the Pd­(II)/Sc­(III) core was a diacetate-bridged heterometallic unit as well as that in previous studies. ,, The presence of the Pd­(II)/Sc­(III) core in 2 , 3 , and 4 was also indicated by 19 F NMR studies that showed their identical 19 F chemical shifts to that of Pd­(OAc) 2 /Sc­(OTf) 3 in MeCN, thus indicating that they had the identically chemical environment (see Figure S60 in the Supporting Information for details). The Pd­(II)/Sc­(III) core was linked to 1a through its directing N -carbonyl group with unsymmetrical η 2 -coordination at the aromatic C 1  C N bond, which caused the chemical shift of H1 significantly upshifting from 7.26 to 7.03 ppm due to the shielding effect of Pd­(II), while H2 and H3 slightly downshifted from 6.99 and 6.84 ppm to 7.08 and 6.89 ppm, respectively, due to the corresponding deshielding effect.…”
Section: Resultssupporting
confidence: 60%
“…In investigating Lewis acid (LA)-modulated catalytic oxidation by redox metal ions, we even unexpectedly found that the LA properties of the Cu 2+ cation play a significant role in Pd­(II)-catalyzed Wacker-type oxidations in addition to its redox properties . This finding inspired us to define Pd­(II)/LA catalysis for organic synthesis, in which the binding of LA to the Pd­(II) cation through the diacetate bridge can substantially improve its catalytic activity . Notably, Yu, Wu, and Houk also proposed an acetate-bridged heterometallic Pd­(II)/Ag­(I) structure through DFT calculations for their Pd­(II)-catalyzed C–H activation with Ag­(I) salt as the oxidant .…”
Section: Introductionmentioning
confidence: 98%
“…Inspired by the finding of the LA promoted Wacker-type oxidations by Pd(OAc) 2 in our previous studies, which were even more efficient than Pd(II)/Cu(II) oxidation, 26 we outlined the Pd (II)/LA catalysis pathway for use in organic synthesis. This Pd (II)/LA catalysis could not only be applied in versatile Pd(II)-catalysed syntheses by aromatic C-H activation with dioxygen as the sole oxidant, [27][28][29][30][31][32][33] it could also be applied in nitrile hydration with water and alkyne oxidation with DMSO, in which Pd(II)/LA functioned as the Lewis acid catalyst. 34,35 In this Pd(II)/LA catalysis, the linkage of the LA to the Pd(II) species by a diacetate bridge sharply improved its catalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…So far, this catalysis has been applied in a list of organic syntheses, [6] including one most recent work on oxidative C−H olefination/annulation to construct dihydrophenanthridines, [7] and expanded to Ni(II)/LA catalyzed S−P bond formation [8] . Particularly, in these Pd(II)/LA catalysis, versatile intermediates from different reactions, including the long‐missing agostic hydrogen intermediate in aromatic C−H activation, were identified through in situ NMR characterizations which provided multiple mechanistic information for Pd(II) catalysis [6i,j,9] . Remarkably, dioxygen was generally employed as the sole oxidant in those oxidation‐involved syntheses which makes them more applicable.…”
Section: Introductionmentioning
confidence: 99%